Bone marrow mesenchymal stem cells stimulated by bFGF up-regulated protein expression in comparison with periodontal fibroblasts in vitro - Colenci, Renato [UNESP]; Silva Assuncao, Luciana Reichert da; Mogami Bomfim, Suely Regina [UNESP]; Golim, Marjorie de Assis [UNESP]; Deffune, Elenice [UNESP]; Penha Oliveira, Sandra Helena [UNESP] (Elsevier B.V., 2014)
Objective: The aim of this study was to evaluate, in vitro, the role of bFGF in the proliferation and expression of collagen type I and fibronectin of dog bone marrow mesenchymal stem cells (dBMMSCs) in comparison with the expression of the same proteins in dog periodontal fibroblasts (dPLFs).Design: dBMMSCs from the iliac crest were cultivated in Dulbecco's Modified Eagle's Medium (DMEM). Flow cytometry analysis (FCA) was used to characterize dBMMSC. Cells were stimulated with bFGF (1, 5 and 10 ng/mL) after 24 and 48 h. Real time RT-PCR was performed to verify collagen type I and fibronectin expressions. MTT assay was used to confirm cellular proliferation. Statistical analyses were performed (ANOVA and Kruskal Wallis tests; p < 0.05).Results: FCA showed 55.98% of CD34+ and 32.67% of CD90+ after bone marrow aspiration; 3.33% of CD34+ and 33.0% of CD90+ before P1. After P2, 10.54% of dBMMSCs expressed CD90, whereas after P3, this number decreased to 1.58%. dPLFs presented 4.04% of CD90+ and 1.05% of CD34+ after P3. MU evaluation showed increase in dBMSC proliferation with 5 ng/mL bFGF-stimulus after 24-h. Both collagen land fibronectin expression were very similar between the two cells groups after 24-h stimulation with 1 ng/mL bFGF concentration. Fibronectin and collagen I expressions were higher after 24-h stimulation with 5 ng/mL bFGF.Conclusion: dBMMSCs (1 ng/mL-bFGF stimulus after 24 h) are very similar to dPLFs as regards morphological and immunostaining characteristics, and collagen and/or fibronectin production. The dBMMSCs presented the highest protein expression rates with 5 ng/mL-bFGF stimulus after 24-h. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Bone marrow; Mesenchymal stem cells; Periodontal ligament; Fibroblasts; bFGF